Analisis Makna Konotatif dan Perubahan Makna Kata “Viral” dalam Berita Media Online - Eman Sulaeman (Metonimia: Jurnal Sastra dan Pendidikan Kesusastraan, 2023)
Abstract This study is motivated by the use of the word viral which is often used to attract the latest information in online news media. The problem discussed is the analysis of connotative meaning and changes in meaning towards the use of the word viral. The purpose of this study is to explain the connotative meaning and changes in meaning towards the use of the word viral in online media. The research method used is descriptive qualitative. Based on the results of the discussion, it was found that lexically, in terms of the meaning of the word viral, it has a negative connotation. Meanwhile, the change in meaning that occurred in the viral news headline was